An Alternative Approach to the Fracture Toughness of Dual Phase Steels - Ulu, S.; Aytekin, H.; Said, G. (Проблемы прочности, 2013)
In this study, the effects of ferrite morphology and of ferrite volume fraction on the mechanical properties and the fracture toughness values ( ) KIc of dual phase steels were investigated. The fracture toughness values were determined using an approach that was different from the standard one. A homogenization heat treatment was applied to the steels. Two different starting microstructures were then obtained by either the full annealing of or the quenching of the steels from austenite before applying intercritical annealing to the steels in the austenite region. After this process, dual phase steels with two types of morphology, coarse and fine, were obtained with 40, 20, and 10% ferrite volume fractions, depending on the starting microstructure. Tempered specimens with 10% ferrite exhibited improved fracture toughness values compared with those of the other steels. Исследуется влияние морфологии структуры феррита и его объемного содержания на
механические свойства и вязкость разрушения двухфазных сталей. Для определения значений
вязкости разрушения использовали не стандартный, а альтернативный подход. Стали подвергали гомогенизирующей термообработке. Путем полного отжига или закалки сталей из
аустенитного состояния до применения докритического отжига в аустенитной области
получены две различные исходные микроструктуры. Получены двухфазные стали с двумя
типами морфологии (крупно- и мелкозернистая) с 40-, 20- и 10%-ным объемным содержанием
феррита в зависимости от исходной микроструктуры. Отпущенные образцы с 10%-ным
объемным содержанием феррита имели более высокие значения вязкости разрушения по
сравнению с таковыми других образцов из этих сталей Досліджується вплив морфології структури фериту та його об’ємного вмісту
на механічні властивості і в’язкість руйнування двофазних сталей. Для визначення значень в’язкості руйнування використовували не стандартний, а альтернативний підхід. Сталі піддавали гомогенізуючій термообробці. Шляхом повного відпалу або загартування сталей з аустенітного стану до використання
докритичного відпалу в аустенітній області отримано дві різні початкові
мікроструктури. Отримано двофазні сталі з двома типами морфології (великоі дрібнозеренна) з 40-, 20- і 10%-ним об’ємним вмістом фериту в залежності
від початкової мікроструктури. Відпущені зразки з 10%-ним об’ємним вмістом фериту мали більш високі значення в’язкості руйнування порівняно з
такими інших зразків із цих сталей.